If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(4x + -2) + 2(10 + -2x) = 3(5x + 1) + -1 Reorder the terms: 5(-2 + 4x) + 2(10 + -2x) = 3(5x + 1) + -1 (-2 * 5 + 4x * 5) + 2(10 + -2x) = 3(5x + 1) + -1 (-10 + 20x) + 2(10 + -2x) = 3(5x + 1) + -1 -10 + 20x + (10 * 2 + -2x * 2) = 3(5x + 1) + -1 -10 + 20x + (20 + -4x) = 3(5x + 1) + -1 Reorder the terms: -10 + 20 + 20x + -4x = 3(5x + 1) + -1 Combine like terms: -10 + 20 = 10 10 + 20x + -4x = 3(5x + 1) + -1 Combine like terms: 20x + -4x = 16x 10 + 16x = 3(5x + 1) + -1 Reorder the terms: 10 + 16x = 3(1 + 5x) + -1 10 + 16x = (1 * 3 + 5x * 3) + -1 10 + 16x = (3 + 15x) + -1 Reorder the terms: 10 + 16x = 3 + -1 + 15x Combine like terms: 3 + -1 = 2 10 + 16x = 2 + 15x Solving 10 + 16x = 2 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 10 + 16x + -15x = 2 + 15x + -15x Combine like terms: 16x + -15x = 1x 10 + 1x = 2 + 15x + -15x Combine like terms: 15x + -15x = 0 10 + 1x = 2 + 0 10 + 1x = 2 Add '-10' to each side of the equation. 10 + -10 + 1x = 2 + -10 Combine like terms: 10 + -10 = 0 0 + 1x = 2 + -10 1x = 2 + -10 Combine like terms: 2 + -10 = -8 1x = -8 Divide each side by '1'. x = -8 Simplifying x = -8
| (y-3)(5y+10)=0 | | (8x+4)(6x-3)=0 | | 5(2t-4)=40-5t | | 6-2x=6x-10x+2+4 | | x(x-3)-9=0 | | y=x^2+2x-6 | | k-5k-25=4 | | 8(5)+3(5)=0 | | 7s+s-4= | | 7y-24=-29+8y | | 9x-5x=8 | | 7n-24=-78+n | | 5x^2+9x-12=23-9x | | 2(1)+3(-2)=-4 | | 8=y-18 | | 2/7(21y+14)-2(4y+3)=0 | | 9x^2+12x+3=0 | | -5-3=17 | | 0.02x+0.01(5000-x)=81 | | x^2+15x-50=0 | | 0.02x+0.01(5000-x)=0.01 | | x^2-15x-50=0 | | 2/7(21y+14)-2(4y+4)=0 | | 4(4x-6)=2(8x+3) | | 3(z-21)+2(z-2)=28 | | 2x-6=5x+18 | | 7(3x-5)+4(15-3x)=2(4x+4)-3 | | 5-3x^2+5x-7=2x+1 | | 5z+4(4-z)=-(z-3)+11 | | 5(x-6)-7(x+2)=-14 | | 50+5x=3x^2 | | 3z-4(z+1)=-(7z+4)+z |